Highly dynamic and sensitive NEMOer calcium indicators for imaging ER calcium signals in excitable cells - Wenjia Gu; Jia-Hui Chen; Yiyin Zhang; Zhirong Wang; Jia Li; Sijia Wang; Hanhan Zhang; Amin Jiang; Ziyi Zhong; Jiaxuan Zhang; Ze Xu; Panpan Liu; et al. (Nature Communications)
Abstract The Endoplasmic/sarcoplasmic reticulum (ER/SR) is central to calcium (Ca2+) signaling, yet current genetically encoded Ca2+ indicators (GECIs) cannot detect elementary Ca2+ release events from ER/SR, particularly in muscle cells. Here, we report NEMOer, a set of organellar GECIs, to efficiently capture ER Ca2+ dynamics with increased sensitivity and responsiveness. NEMOer indicators exhibit dynamic ranges an order of magnitude larger than G-CEPIA1er, enabling 2.7-fold more sensitive detection of Ca2+ transients in both non-excitable and excitable cells. The ratiometric version further allows super-resolution monitoring of local ER Ca2+ homeostasis and dynamics. Notably, NEMOer-f enabled the inaugural detection of Ca2+ blinks, elementary Ca2+ releasing signals from the SR of cardiomyocytes, as well as in vivo spontaneous SR Ca2+ releases in zebrafish. In summary, the highly dynamic NEMOer sensors expand the repertoire of organellar Ca2+ sensors that allow real-time monitoring of intricate Ca2+ dynamics and homeostasis in live cells with high spatiotemporal resolution.